A short history of linguistics / Linguistics - Robins, R. H. (Robert Henry) (London ; New York : Longman, 1997)
This complete revision and updating of Professor Robins' classic text offers a comprehensive account of the history of linguistic thought from its European origins some 2500 years ago to the present day. It examines the independent development of linguistic science in China and Medieval Islam, and especially in India, which was to have a profound effect on European and American linguistics from the end of the eighteenth century.
Readable and authoritative, Professor Robins' introduction provides a clear and up-to-date overview of all the major issues in the light of contemporary scholarly debate, and will be essential reading for undergraduate and graduate students of linguistics alike.
1. Introduction -- 2. Greece -- 3. Rome -- 4. The Middle Ages -- 5. The Renaissance and after -- 6. The eve of modern times -- 7. Comparative and historical linguistics in the nineteenth century -- 8. Linguistics in the twentieth century: first period -- 9. Linguistics in the twentieth century: second period.
Includes bibliographical references and index.
Keywords: Linguistics -- History